Medical research and ethics - Revisited - Thakkar, P; Shringarpure, K S; Gupte, S; Agrawal, A (Indian Journal of Child Health, 2018)
Ethics in the medical research is known since many years; however, there have been new developments in this area recently. A phenomenal improvement in the health-care system, leading to increased life expectancy, and thereby, newer lifestyle and other health-related diseases has opened avenues for newer drugs and health-care technology. However, these have to be tried and tested in the context of the disease epidemiology, health-care delivery and of course, medical ethics. Monitoring and evaluation of the treatment regimes of well documented effective medicines is also required. This is the core of medical research. With the ever increasing concept of evidence-based medical system, and thereby, a rapid rise in the number of clinical trials; the role of medical ethics is potentially increasing to keep the patients